Pewarisan Menurut Hukum Waris Islam Terhadap Sistem Kekerabatan Matrilineal Minangkabau - Ira Damayanti Putri; Dhea Amelisca; Sarfia Nengsih (Fakultas Hukum Universitas Airlangga, 2019)
Minangkabau indigenous people if the family does not have children, especially children, especially girls, it is permissible to adopt children as successors. The position of daughters in the family in the Minangkabau community is very important in terms of the continuation of the clans from a family, this is because the Minangkabau people generally adhere to the Matrilineal family system. But in its development with the entry of Islam in Indonesia, most of the Minangkabau people were influenced by the teachings of Islam, so that in the position of heirs there was a position of heirs that contradicted the Islamic inheritance law with customary inheritance law in the Minangkabau community. The problem in this research is Islamic inheritance law towards customary inheritance law in Minangkabau people. The results of this study are that the Minangkabau community after the entry of Islam, implemented two inheritance systems, namely for high inheritance inherited by the Matrilineal collective inheritance system, for low inheritance inherited with Bilateral individual inheritance systems.